Lithium storage properties of in situ synthesized Li2FeSiO4 and LiFeBO3 nanocomposites as advanced cathode materials for lithium ion batteries. Issue 46 (22nd October 2015) - Hu, Lin; Yang, Jinlong; Amiinu, Ibrahim Saana; Kang, Xiaochun; Zhang, Wei; Mu, Shichun
Abstract : The kinetics towards charge transfer and lithium ion diffusion are effectively enhanced with in situ adding small amounts of LiFeBO3, leading to a remarkably improved charge–discharge performance of Li2 FeSiO4 as advanced cathode materials for lithium ion batteries. Abstract : (1 − x )Li2 FeSiO4 · x LiFeBO3 /C ( x = 0, 0.02, 0.05, 0.08, 0.12, and 1.00) hetero-grains are successfully synthesized via an in situ citric acid-based sol–gel method and evaluated as cathode materials for lithium ion batteries. As a result, 0.92Li2 FeSiO4 ·0.08LiFeBO3 /C delivers an optimum discharge capacity of 251 mA h g −1 which corresponds to nearly 1.51 Li + intercalation per molecule. Furthermore, a capacity retention of 104.5% after 5 cycles at 0.1 C is attained, and a value of 188.3 mA h g −1 (approaching 1.13 Li + intercalation per molecule) remains even after one hundred cycles at 1 C. In particular, at a high-rate of 10 C, there is almost no capacity decline even after 500 cycles, indicating an excellent cycling stability. The greatly improved electrochemical lithium storage properties of the novel in situ hybridized materials can be attributed to the enhanced kinetics towards Li + diffusion and electron transport compared with that of pure Li2 FeSiO4 /C electrodes.